Credit requirements for agriculture. - National Council of Applied Economic Research (New Delhi : National Council of Applied Economic Research, 1974)
This book is on Indian agriculture, the historical experience of great dependence on credit, the cost of which has tended to subject small farmers, who form the majority, to an increasing burden of debt.
Chiefly tables.
ucj, 14/01/2019
Loans
Keywords: Agricultural credit